The image of Ukrainian ethnic culture through the context of novels of Maria Matios "Solodka Darusia", "Hardly Ever Otherwise" - Zviahina, H. O.; Pototska, O. I.; Звягіна, Ганна Олександрівна; Потоцька, Олена Іванівна (My University, 2023)
In this article, we analyze the image of Ukrainian ethnic culture through the context of novels of Maria Matios “Solodka Darusia”, “Hardly Ever Otherwise”. The main goal is to discuss the reflection of Ukrainian ethnic culture in the works of Maria Matios. We aim to discuss the important role of providing identity for individual human beings, original model of the M. Matios world.
Keywords: ethnic culture; ethnic renaissance; national identity; sacral; stereotypes